Effect of Corporate Social Responsibility on Financial Performance in Nigeria - Joy Itoya; P.A. Akhator; Innocent Chiawa Igbokwe; Cletus Owuze (European Scientific Journal, ESJ, 2022)
The study examined corporate social responsibility on financial performance of banks in Nigeria by using earning per share, gross earning and profit after tax as measures of financial performance of banks in Nigeria. The study design was ex-post-facto. Pearson correlation and simple regression analysis were the major statistical tools used for the analysis through the application of SPSS version 20.0 and E-View 8.0 software packages. Correlation results showed that whereas the relationship between corporate social responsibility and earning per share was positive but insignificant, it showed strong, positive and significant relationships with gross earning and profit after tax respectively. Similarly, corporate social responsibility expenditure was found to have insignificant effect on earnings per share, it has significant effect on gross earning and profit after tax of the banks in Nigeria. The study recommends among others that corporate organizations should endeavor to give more to the society in CSR and leverage it to enhance the financial performance of their businesses in the country.